Pengaruh Financial Distress, Corporate Social Responsibility Dan Struktur Modal Terhadap Nilai Perusahaan - Merlinda Merlinda; Wulandari Cahyani Putri (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to determine the influence of Financial Distress, Corporate Social Responsibility and Capital Structure between periods on Company Value. The population in this research is non-cyclical consumer companies listed on the Indonesia Stock Exchange in 2019-2023. The type of research used in this research is an associative method with a quantitative approach. The sample selection procedure used was purposive sampling. The data analysis technique used is descriptive Statistics and panel data regression analysis using Eviews 10 software. The analytical tools used are panel data regression model selection, classical assumption model testing, coefficient of determination, hypothesis testing. Based on the research results, it was found that: Financial Distress, Corporate Social Responsibility and Capital Structure together have an influence on Company Value. Partially, Financial Distress has an effect on Company Value, Corporate Social Responsibility has an effect on Company Value and Capital Structure has no effect on Company Value.